The Evolution of FDI in the Context of Globalization - Valeriu Laurenţiu Onose; Ecaterina Necşulescu (EIRP Proceedings, 2015)
The importance of studying globalization under its most important aspects in economic terms is relevant in terms of the major influences that determine them as operating environment, development and manifestation of a country’s economy. Globalization is a current, continuous process, accompanying the evolution of the society, the changes they produce are different from those prevailing in the first decades after the second world war. In the specialized literature there are presented the views according to which globalization can be defined in different ways depending on the considered level. In accordance with these views, we may speak of the globalization of the world, into a single country, of a certain industry, of a corporation or a business relationship or functions within a company. In our paper globalization refers to increasing the economic interdependence between countries, reflected by increasing the cross-border flows of goods and services, capital and know-how, the volume of incoming and outgoing flows of foreign direct investments. At the level of a certain country, globalization refers to the extension of the interconnections between the economy of a country and the rest of the world. In this regard, it is noteworthy that, despite the increasingly globalized world, not all states are equally integrated into the global economy.